Growing together personal relationships across the lifespan - Lang, Frieder R. 1962-; Fingerman, Karen L. (Cambridge University Press, 2004)
Understanding personal relationships throughout the life course is one of the most crucial issues in the behavioral and social sciences. This book brings together perspectives from different disciplines on individual development and personal relationships across the life span. The book addresses two pertinent dimensions of personal relationships: 1) structures of relationship networks (e.g. kin vs. non-kin, peripheral vs. intimate, short-term vs. long-term) and 2) processes (i.e. change or stability) and outcomes of personal relationships across the life span. The book stimulates discussion of personal relationships as resources for and outcomes of individual development throughout the life course. Different qualities of personal relationships serve as catalysts for individual development. At the same time, relationship qualities reflect changes of developing individuals. The book does not give exclusive priority to one phase of the human life span. Rather, each chapter addresses social development across the entire life span from childhood to later adulthood
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Interpersonal relations; Developmental psychology; Entwicklungspsychologie; Zwischenmenschliche Beziehung; Aufsatzsammlung